Promotion of water-mediated carbon removal by nanostructured barium oxide/nickel interfaces in solid oxide fuel cells - Yang, Lei (Nature Publishing Group, 2011)
The existing Ni-yttria-stabilized zirconia anodes in solid oxide fuel cells (SOFCs) perform poorly in carbon-containing fuels because of coking and deactivation at desired operating temperatures. Here we report a new anode with nanostructured barium oxide/nickel (BaO/Ni) interfaces for low-cost SOFCs, demonstrating high power density and stability in C3H8, CO and gasified carbon fuels at 750°C. Synchrotron-based X-ray analyses and microscopy reveal that nanosized BaO islands grow on the Ni surface, creating numerous nanostructured BaO/Ni interfaces that readily adsorb water and facilitate water-mediated carbon removal reactions. Density functional theory calculations predict that the dissociated OH from H2O on BaO reacts with C on Ni near the BaO/Ni interface to produce CO and H species, which are then electrochemically oxidized at the triple-phase boundaries of the anode. This anode offers potential for ushering in a new generation of SOFCs for efficient, low-emission conversion of readily available fuels to electricity.